A GEOGRAPHIC APPROACH TO MEASURING AND ORGANISING AFFORDABLE MEDICAL AND THERAPEUTIC TOURISM FOR PEOPLE WITH DEMENTIA - Semenova, Zoya A.; Chistobaev, Anatoliy I.; Dildina, Valeriya P. (Quaestiones Geographicae, 2020)
The article covers the geographical features of the organisation of medical tourism for a group of the world’s population suffering from a brain disease – dementia. The main attention is paid to the development of this type of tourism in Russia in comparison with some other countries. The question is raised about the involvement of these people in tourism activities, which could help to improve their health status and improve the living environment of societies. The main problems faced by tourists with the disease dementia are considered. The authors advocate that freedom of movement is the inalienable right of every person. Therefore, the creation of conditions for comfortable travel of people even with mental defects becomes a necessary measure to ensure the sustainable development of accessible tourism infrastructure. The recommendations are given, the implementation of which will allow organising an efficiently working tourist and recreational system that satisfies the needs of these peculiar recreational tourists, as well as the interests of all society representatives.